Konflik Antara Primkop Kartika B-05 dan Kopada dalam Penyelenggaraan Angkutan Desa di Kabupaten Purworejo - Margareta Ega Rindu Suryaningtyas; Turtiantoro .; Lusia Astrika (Journal of Politic and Government Studies, 2015)
Conflict related organization of freight villages that already lasted 13 years indicates a failure of the Government of its obligations in Purworejo organizes freight village in accordance with the mandate of the ACT No. 22 of 2009 and law No. 10 year 2012 about Traffic and Road Transport. Because it is clearly mentioned as a mandate for the Government to uphold the law, provided the right of every individual and the group, as well as the realization of a prosperous society order Purworejo, faithful, honest, fair, independent, and appropriate patriotic vision Purworejo -civil society-.To uncover the problem and research objectives researchers using qualitative descriptive approach eksplanatori. Data analysis was conducted using data analysis deskriptif-kualitatif. The purpose of this research was to determine the occurrence of conflict and stake holder's involvement in organizing freight village. Data obtained then used to formulate recommendations as a solution to the conflict.Research results are found, the situation showed that the conflict originated from the inception of the Government policy related transport rejuvenation Purworejo village in 1988. At the range in 2001 Primkop Kartika B-05 (lines 19 and 20) performs line by cutting the routes of aggravated trespass Kopada (line B), human error is the driver who later became cultures breaking-, the difference of perception between the respective parties in conflict related causes of conflict, conflict between stake holder which stem from a conflict of interest between economics and politics result ed in not optimal roles of institutions and relevant agencies in an attempt to resolve the conflict. Patterns of institutional policy and related institutions that leads to political salvation becomes the best efforts that can be made during the 13 years of the conflict.In an effort of conflict resolution, the recommendation can be given i.e.: increase coordination, cooperation and commitment of the parties involved in organizing the transport of the village, make regulations giving legitimacy in enforcement policy, programs, and activities to support the efforts of conflict resolution. Furthermore local governments through authorized institutions do of socialization on the recommendation of conflict resolution to all associations conduct construction of the freight village, especially the parties involved conflict i.e. Primkop Kartika B-05 and Kopada.